Parents' involvement with children's homework: a case study of academicians in a Malaysian institution of higher learning - Abdullah, Liza; Abdullah, Hazlina; Hashim, Che Noraini (Scottish Group of Education and Testing Services, 2014)
Many parents categorised homework as an additional burden on top of the normal class room activities. A small group of parents however appreciates the concept of homework as they believe it could enhance students’ discipline and academic performance. This study examines the role played by parents in helping their children to complete school’s homework. It aimsto identify the methods and frequency of assistance given to children. The study also looks at the parents’ perception while helping their children to complete homework and to trace the relationships between variables including parental feelings of efficacy, frequency of parental assistance and the amount of homework completed. In gathering information and data, a quantative methodology through online survey was employed. From a total of 56 respondents who are academicians from the International Islamic University Malaysia (IIUM) , the study revealed the following findings: i) Provision of structure is at the top of the list of assistance provided by parents, followed by direct involvement and autonomy of supports. ii) With the amount of homework the children were able to complete, no significant relationship between the frequency of assistance and the children age was found. It is concluded that respondents’ self-efficacy is a factor in assisting their children to complete homework. This study expects a more systematic predictive model which could be designed on matters relating to parents’ assistance in completing homework given to their children.